Improving the Behavior of Children With Fetal Alcohol Spectrum Disorders. (November 2021) - Hutton, Laura
Prenatal exposure to alcohol causes a pattern of brain-based deficits and is associated with behavioral challenges (Wozniak et al., 2019). Understanding the neurocognitive behaviors common among individuals with fetal alcohol spectrum disorders (FASD) can increase teachers' effectiveness (Tremblay et al., 2017). Environmental changes, such as modifying the classroom, providing high levels of structure, and increasing adult supervision, have been shown to improve the behavior of individuals with FASD (Bohjanen et al., 2009). There is also emerging evidence that explicit instruction in metacognitive strategies is effective with this population (Makela et al., 2019. Students with FASD can benefit from being explicitly taught to stop and think before acting and to use rehearsal, memory aids, and positive self-talk.